2016
DOI: 10.5811/westjem.2016.6.30690
|View full text |Cite
|
Sign up to set email alerts
|

Increased 30-Day Emergency Department Revisits Among Homeless Patients with Mental Health Conditions

Abstract: IntroductionPatients with mental health conditions frequently use emergency medical services. Many suffer from substance use and homelessness. If they use the emergency department (ED) as their primary source of care, potentially preventable frequent ED revisits and hospital readmissions can worsen an already crowded healthcare system. However, the magnitude to which homelessness affects health service utilization among patients with mental health conditions remains unclear in the medical community. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…Some studies attempted to use validated questionnaires for material needs. Most studies were cross‐sectional surveys, five were retrospective cohort studies, and three used prospective cohorts . Several studies described their methods as “case‐control” or “prospective” but were in fact cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies attempted to use validated questionnaires for material needs. Most studies were cross‐sectional surveys, five were retrospective cohort studies, and three used prospective cohorts . Several studies described their methods as “case‐control” or “prospective” but were in fact cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Local studies reported higher rates of homelessness than studies using NHAMCS. While the majority of local studies reported figures between 2.5 and 6%, homelessness rates were significantly higher in studies among high‐risk alcohol and drug users (22.8%), patients with psychiatric diagnoses in Arizona (22.3%), and patients at a public hospital ED near a homeless shelter in New York City (13.8%) . Several studies found an association between homelessness status and health services use (e.g., frequent ED use, hospital readmissions) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). One American study, which examined hospital‐based service use 30‐days posthospital discharge found that rates of emergency department use and hospital readmission were higher among people experiencing both homelessness and mental illness as compared to other subpopulations (Lam, Arora, and Menchine ). Additionally, previous studies have found that among individuals with mental illnesses, while less likely to seek medical services overall, are more likely to seek medical care from urgent care settings (i.e., emergency departments) rather than via community‐based primary care (Pines et al.…”
Section: Discussionmentioning
confidence: 99%
“…). An American study found that the experience of homelessness and having a mental illness interacted to produce even higher levels of emergency department use and hospital readmission compared to those experiencing homelessness alone, mental illness alone, or neither (Lam, Arora, and Menchine ). More broadly, research findings have stimulated advocacy for increased emphasis and investments in continuity of care.…”
mentioning
confidence: 99%